Development of Integrated Science Teaching Materials on Energy and Environment Themes to Improve Reading Literacy and Numerical Ability - Handayani, Maria Theresia Sri; Sinaga, Parlindungan; Liliawati, Winny (FKIP Universitas Lampung, 2022)
Integrated science learning is expected to be able to prepare students to have 21st century skills, especially literacy skills needed to meet the needs of these students. This research is motivated by the limited number of science teaching materials that are presented in an integrated manner with the theme of Energy and Environment. This study aims to test the feasibility of integrated science teaching materials for seventh grade junior high school students using the ADDIE method. This research was conducted in a private junior high school in Bandung. The instruments used are quality tests and tests of understanding of teaching materials. The validator tested the quality of teaching materials on 2 expert lecturers and 10 junior high school science teachers and the test of understanding the main ideas of the discourse was given to 26 students. The data analysis technique used descriptive statistics. The results of data analysis showed that the results of the quality test of teaching materials were 83.51% in the very feasible category and the results of the comprehension test of the main ideas of the discourse obtained 72.17% in the high category. The average quality test and understanding test obtained 77.84%. From this research, it can be concluded that the integrated science teaching materials are appropriate to be used as independent teaching materials that equip reading literacy skills and numeracy skills. Keywords: science teaching material, reading literacy, numerical ability. DOI: http://dx.doi.org/10.23960/jpmipa/v23i2.pp723-733